PCB 118-induced endothelial cell apoptosis is partially mediated by excessive ROS production. (13th June 2017) - Tang, Li; Cheng, Jin-nan; Long, Yang; He, Xue-mei; Liang, Guan-nan; Tang, Xiao-ping; Jiang, Chun-xia; Chen, Feng
Abstract: Endothelial cell apoptosis, which may alter the integrity of the endothelium and lead to plaque instability, plays a critical role in the development and pathogenesis of atherosclerosis. Exposure of polychlorinated biphenyls (PCBs) is associated with increased risk of atherosclerosis and cardiovascular disease. In our present study, we explored whether exposure to PCB 118 influences endothelial cell apoptosis in vitro and the underlying mechanisms involved. As expected, exposure to PCB 118 increased the intracellular reactive oxygen species (ROS) levels in HUVECs. Increases in apoptosis and Bax/Bcl-2 ratios were observed in PCB 118-treated HUVECs. N-acetyl-l -cysteine (NAC), a ROS scavenger, partially reduced PCB 118-induced apoptosis and Bax/Bcl-2 ratios in HUVECs. Taken together, PCB 118-induced endothelial cell apoptosis was partially initiated by excessive ROS production.